2019
DOI: 10.3389/fmicb.2019.00652
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals the Biocontrol Mechanism of Bacillus velezensis F21 Against Fusarium Wilt on Watermelon

Abstract: The watermelon ( Citrullus lanatus ) is one of the most important horticultural crops for fruit production worldwide. However, the production of watermelon is seriously restricted by one kind of soilborne disease, Fusarium wilt, which is caused by Fusarium oxysporum f. sp. niveum (Fon). In this study, we identified an efficient PGPR strain B. velezensis F21, which could be used in watermelon produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…B. amyloliquefaciens L3 can control Fon by producing diffusible and volatile organic compounds (Wu et al ., 2019). B. velezensis F21 can induce systemic resistance to Fon in watermelon through related genes and phytohormone signalling factors (Jiang et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…B. amyloliquefaciens L3 can control Fon by producing diffusible and volatile organic compounds (Wu et al ., 2019). B. velezensis F21 can induce systemic resistance to Fon in watermelon through related genes and phytohormone signalling factors (Jiang et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(dominant microbes). The relative abundance of Trichoderma and Bacillus that have been widely used as a biological control agent against various pathogens were no difference between control samples and S-FOM samples [15,16,17,18]. But, the relative abundance of T. asperellum, T. atroviride, B. anthracis, B. kochii, and so on showed an increased tendency in response to the invasion of F. oxysporum.…”
Section: Discussionmentioning
confidence: 89%
“…and Bacillus spp. [15,16,17,18]. Several studies of biocontrol agents have been reported combination treatment methods using two or more of these agents are more effective in managing the disease than treatment using a single biocontrol agent.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, a resistant cultivar of banana had an inherently higher capacity to stimulate POD production than a susceptible cultivar ( Aguilar et al, 2000 ). Moreover, B. velezensis can trigger basal immunity in plants ( Jiang et al, 2018 ) by increasing the expression of plant defense-related genes and the activities of some defense enzymes, such as catalase (CAT) and POD ( Jiang et al, 2019 ). In this study, banana seedlings treated with HN03 had a higher POD content than those in the treatment without HN03, and the highest POD content was detected in the treatment with HN03 combined with wormcast.…”
Section: Discussionmentioning
confidence: 99%